Why We Need Community Engagement in Medical Research. (1st August 2014) - Holzer, Jessica K.; Ellis, Lauren; Merritt, Maria W.
Abstract : Background: The medical research enterprise depends on public recognition of its societal value. In light of evidence indicating public mistrust, especially among minorities, inadequate enrollment as well as diversity of research participants, and poor uptake of findings, medical research seems to fall short of sufficient public regard. Community engagement in medical research, with special attention to minority communities, may help to remedy this shortfall by demonstrating respect for the communities in practical ways. Approach: We provided 3 case examples that illustrate how specific approaches to community-engaged research can build trust between researchers and communities, encourage participation among underrepresented groups, and enhance the relevance as well as the uptake of research findings. Discussion: A common attribute of the specific approaches discussed here is that they enable the researchers to demonstrate respect by recognizing community values and interests. The demonstration of respect for the communities has intrinsic ethical importance. Conclusions: The 2 potential outgrowths of demonstrating respect specifically through community engagement are (1) the production of research that is more relevant to the community and (2) the mitigation of asymmetry in the researcher-community relationship. We summarized practical resources available to researchers who seek to incorporate community engagement in their research.